Design of a High Efficiency Bi-Directional Four-Switch Buck-Boost Converter With HV Gate Driver for Multi-Cell Battery Power Bank Applications - Sung-June Byun; Byeong-Gi Jang; Jong-Wan Jo; Dae-Young Choi; Young-Gun Pu; Sang-Sun Yoo; Seok-Kee Kim; Yeon-Jae Jung; Kang-Yoon Lee (IEEE Open Journal of Circuits and Systems)
This paper presents a bidirectional Four-Switch Buck-Boost (FSBB) converter with a high-voltage (HV) gate driver for use in power bank applications. The proposed FSBB is also integrated into this converter for increased efficiency. Thus, the proposed buck-boost converter can reduce conduction loss over a wide input voltage range by reducing the on-resistance of external MOSFETs using a gate source voltage (VGS) of 5V or 10V. The chip to be examined in this study is fabricated using a 130 nm 1P5M bipolar-CMOS-DMOS HV process with laterally diffused MOSFET (LDMOS) options to have a die size of 2.7 x 2.7 mm2. The proposed architecture is found to achieve a maximum output power level of 40W. The measurement results show that the maximum efficiencies at gate-source voltages (VGS) of 5V and 10V are 96.67% and 98.15%, respectively.